Promoting Middle School Students’ Science Text Comprehension via Two Self-Generated “Linking” Questioning Methods - Sason, Hava; Michalsky, Tova; Mevarech, Zemira (Frontiers in Psychology, 2020)
This quasi-experimental study examined training in two types of reading strategies: self-generated questions either connecting to prior knowledge (Extra-Text) or connecting between the text’s parts (Within-Text). Immediate and long-term effects were assessed on ninth graders’ science text comprehension, versus an untrained control group. The three student groups (N = 193) received the same study unit of scientific texts and accompanying tasks, either with/without training in self-generated questioning. PISA-based science literacy assessments (phenomenon identification, scientific explanation, evidence utilization) were collected at baseline, immediately after intervention, and at 4-month follow-up. Results from both short- and long-term assessments indicated that those learners trained to generate questions about within-text connections reached significantly higher science text comprehension achievements than the other two groups – students trained to generate questions connecting to their prior knowledge and control students who received no support for generating questions. Findings may contribute to the design of support methods and teaching strategies for promoting literacy in general and scientific literacy in particular.